2022
DOI: 10.1002/eap.2585
|View full text |Cite
|
Sign up to set email alerts
|

Species‐level tree crown maps improve predictions of tree recruit abundance in a tropical landscape

Abstract: Predicting forest recovery at landscape scales will aid forest restoration efforts.The first step in successful forest recovery is tree recruitment. Forecasts of tree recruit abundance, derived from the landscape-scale distribution of seed sources (i.e., adult trees), could assist efforts to identify sites with high potential for natural regeneration. However, previous work revealed wide variation in the effect of seed sources on seedling abundance, from positive to no effect. We quantified the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…However, these recent modeling efforts have relied on moderate resolution data such as 30 m burn severity maps from Monitoring Trends in Burn Severity (MTBS, https://www.mtbs.gov/), which may obscure fine-scale variation in seed availability. Fine scale maps of surviving trees, such as those created using fine scale imagery or lidar data, may more accurately reflect the variation in seed source availability on the landscape, and thus more closely represent true seed availability (Barber et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, these recent modeling efforts have relied on moderate resolution data such as 30 m burn severity maps from Monitoring Trends in Burn Severity (MTBS, https://www.mtbs.gov/), which may obscure fine-scale variation in seed availability. Fine scale maps of surviving trees, such as those created using fine scale imagery or lidar data, may more accurately reflect the variation in seed source availability on the landscape, and thus more closely represent true seed availability (Barber et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Continued improvement of segmentation algorithms will potentially improve crownto-crown matching. However, in other cases, models that combine field measurements of mortality for a subsample of plants with large-scale remotely sensed estimates may be necessary for best performance (Barber 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For a single time step, we found that segmentation performed well, including fairly accurate estimates of cover and plant abundance. Counts of individual plants and cover estimates are essential for many ecological applications, from predicting future population growth to measuring potential forage for threatened herbivores (Olsoy et al 2020; Barber et al 2022). Estimating plant population dynamics with remote sensing, including forecasting cover trajectories and population growth rate, will require integrating measurements across years.…”
Section: Discussionmentioning
confidence: 99%
“…Decomposing structural heterogeneity into specific scales boosts the ability of these metrics to predict ecologically relevant outcomes, particularly when multi-scale metrics are included in the same predictive model. Predictions of natural regeneration after disturbance, including recruitment, will aid decision-making on where to allocate limited resources for restoration (Barber et al 2022).…”
Section: Structural Heterogeneity As a Predictor Of Recruitmentmentioning
confidence: 99%